On the Semantics and Pragmatics of Dysfluency - Ginzburg, Jonathan; Fernández, Raquel; Schlangen, David (Proceedings of the Amsterdam Colloquium, 2011)
Although dysfluent speech is pervasive in spoken conversation, dysfluencies have received little attention within formal theories of dialogue. The majority of work on dysfluent language has come from psycholinguistic models of speech production and comprehension (e.g. [10, 3, 1]) and from structural approaches designed to improve performance in speech applications (e.g. [14,8]). In this paper, we present a detailed formal account which: (a) unifies dysfluencies (self-repair) with Clarification Requests (CRs), without conflating them, (b) offers a precise explication of the roles of all key components of a dysfluency, including editing phrases and filled pauses, (c) accounts for the possibility of self-addressed questions in a dysfluency.